Cytochrome P450 oxygenases of Taxol biosynthesis - Kaspera, Rüdiger (2006)
Cytochrome P450 monooxygenases play a prominent role in the biosynthesis of the diterpenoid anticancer drug Taxol, as they appear to constitute about half of the 19 enzymatic steps of the pathway in yew (Taxus) species. A combination of classical biochemical and molecular methods, including cell-free enzyme studies and differential-display of mRNA-reverse transcription polymerase chain reaction (RT-PCR) combined with a homology-based searching and random sequencing of a cDNA library from induced T. cuspidata cells, led to the discovery of six novel cytochrome P450 taxoid (taxane diterpenoid) hydroxylases. These genes show unusually high sequence similarity with each other (>70%) but low similarity (<30%) to, and significant evolutionary distance from, other plant P450s. Despite their high similarity, functional analysis of these hydroxylases demonstrated distinctive substrate specificities responsible for an early bifurcation in the biosynthetic pathway after the initial hydroxylation of the taxane core at C5, leading into a biosynthetic network of competing, but interconnected, branches. The use of surrogate substrates, in cases where the predicted taxoid precursors were not available, led to the discovery of two core oxygenases, the 2α- and the 7β-hydroxylase. This general approach could accelerate the functional analysis of candidate cDNAs from the extant family of P450 genes to identify the remaining oxygenation steps of this complex pathway.